Ba9V3Se15: a novel compound with spin chains. (30th April 2018) - Zhang, Jun; Liu, Min; Wang, Xiancheng; Zhao, Kan; Duan, Lei; Li, Wenmin; Zhao, Jianfa; Cao, Lipeng; Dai, Guangyang; Deng, Zheng; Feng, Shaomin; Zhang, Sijia; et al.
Abstract: In this work, a novel compound Ba9 V3 Se15 with one-dimensional (1D) spin chains was synthesized under high-pressure and high-temperature conditions. It was systematically characterized via structural, magnetic, thermodynamic and transport measurements. Ba9 V3 Se15 crystallizes into a hexagonal structure with a space group of P -6 c 2 (188) and the lattice constants of a = b = 9.5745(7) Å and c = 18.7814(4) Å. The crystal structure consists of face-sharing octahedral VSe6 chains along c axis, which are trimeric and arranged in a triangular lattice in ab -plane. Ba9 V3 Se15 is a semiconductor and undergoes complex magnetic transitions. In the zero-field-cooled (ZFC) process with magnetic field of 10 Oe, Ba9 V3 Se15 sequentially undergoes ferrimagnetic and spin cluster glass transition at 2.5 K and 3.3 K, respectively. When the magnetic field exceeds 50 Oe, only the ferrimagnetic transition can be observed. Above the transition temperature, the specific heat contains a significant magnetic contribution that is proportional to T 1/2 . The calculation suggests that the nearest neighbor (NN) intra-chain antiferromagnetic exchange J 1 is much larger than the next nearest neighbor (NNN) intra-chain ferromagnetic exchange J 2 . Therefore, Ba9 V3 Se15 can be regarded as an effective ferromagnetic chains with effective spin-1/2 by the formation of the V (2) (↓) V (1) (↑) V (2) (↓) cluster.